NOZZLE DAN SUDUT BUANG SUDU TERHADAP DAYA DAN EFISIENSI MODEL TURBIN PELTON DI LAB. FLUIDA - ., Supardi; Prasetya, Endra (MEKANIKA: Jurnal Teknik Mesin, 2015)
Pelton turbine is one of the impulse turbines, wherein the turbine is able to transform the water potentialenergy into kinetic energy by using a nozzle. The water that comes out of the nozzle with high speed at atmosphericpressure hit the bucket which consists of two symmetrical parts. After hit the bucket, the direction of the flowvelocity change resulting in a change of momentum (impulse), consequently rotating turbine wheel generatesmechanical energy. As well as pelton turbine models in laboratory fluid which has been studied by R. HartonoTeguh in his finally task in 2006 on Experimental studies Determining Characteristics of Model Redesign Peltonturbine in Lab. Fluid. Assess experimental this time aimed at the development which also examines the peltonturbine models to determine the effect of variations in the diameter of the nozzle and the angle of the bucket waste ofthe generated power and efficiency. Variation used is the diameter of the nozzle 6 and 9 mm with exhaust bucketangle 145o, 165o, and 175o. Pelton turbine models that were tested using a single nozzle, with a number of buckets22 pieces, as well as using a runner diameter of 150 mm. Dimensional bucket used has several main dimensions,namely the width of the bucket 36 mm, bucket length 27 mm, bucket depth of 8.10 mm, bucket gap width of 10.8 mm,and the distance of the center beam bucket Valentine of 13.5 mm. From the data obtained by tests performed powerand the largest turbine efficiency at variation of 6 mm diameter nozzle at an angle of 175o bucket exhaust i.e. 38.76Watts with an efficiency of 82.80%. The largest generator power can be achieved in the variation of 6 mm diameternozzle at an angle of 175o bucket exhaust i.e. 10.4 Watt, while the best efficiency occurs at the nozzle 9 mm diametervariation with angle of 175o exhaust bucket that is 50.61%.Keywords: Pelton Turbine, and Power Efficiency